2018
DOI: 10.1128/mcb.00252-18
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAcylation Signal Mediates Proteasome Inhibitor Resistance in Cancer Cells by Stabilizing NRF1

Abstract: Cancer cells often heavily depend on the ubiquitin-proteasome system (UPS) for their growth and survival. Irrespective of their strong dependence on the proteasome activity, cancer cells, except for multiple myeloma, are mostly resistant to proteasome inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 68 publications
3
67
1
Order By: Relevance
“…It seems possible that the Nrf2-sMaf heterodimer forms stable complexes only when it interacts with particular neighboring transcription factors or when it interacts with the promoter complexes through appropriate transcriptional cofactors. Since it has been reported that Nrf1 and Nrf2 recruit different transcriptional cofactors to exert their transactivation activities (49)(50)(51), these cofactors may also confer target gene specificity to these CNC factors.…”
Section: Discussionmentioning
confidence: 99%
“…It seems possible that the Nrf2-sMaf heterodimer forms stable complexes only when it interacts with particular neighboring transcription factors or when it interacts with the promoter complexes through appropriate transcriptional cofactors. Since it has been reported that Nrf1 and Nrf2 recruit different transcriptional cofactors to exert their transactivation activities (49)(50)(51), these cofactors may also confer target gene specificity to these CNC factors.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer cells, Nrf1 can be stabilized by OGT through O-GlcNAcylation at Ser448 and Ser451, a modification that suppresses the ubiquitinproteasome mediated degradation of Nrf1. In contrast, reduced expression of Nrf1 suppresses its invasion and migration ability (115,128). In summary, crosstalk between O-GlcNAcylation and other PTMs plays critical roles in regulating cancer metastasis.…”
Section: Interplay Between O-glcnacylation and Other Ptms In Cancer Mmentioning
confidence: 99%
“…Thus, Nrf1 is critically implicated in a variety of important physio-pathological processes by governing expression of crucial genes in order to reinforce antioxidant, detoxification and cytoprotective responses to cellular stress. Of clinical interest, Nrf1 mediates the proteasomal 'bounce-back' response, leading to drug resistance to proteasomal inhibitors for clinical treatment of neuroblastoma, multiple myeloma and triple-negative breast cancers (Steffen et al, 2010;Bugno et al, 2015;Sekine et al, 2018). During its translation, Nrf1 is targeted to the endoplasmic reticulum (ER) and subject to extensive post-translational modification before it regulates its target genes.…”
Section: Toxicology and Pharmacologymentioning
confidence: 99%